An analysis of mobile banking acceptance by Malaysian customers - Hanudin, Amin; Baba, Ricardo; Mohd Zulkifli Muhammad, (Sunway University College, 2007)
Today, the advancement of mobile technologies has provided an opportunity for financial providers in introducing new financial innovations. One of the emerging financial innovations introduced by financial providers is mobile banking. This study adopts a technology acceptance model (TAM) to investigate factors that determine an individual?s intention to use mobile banking among bank customers in Labuan and Kota Kinabalu. The TAM includes perceived credibility, perceived self-efficacy and normative pressure. Our results support the extended TAM in predicting bank customers? behavioural intention to use mobile banking. Determinants are perceived usefulness, perceived ease of use, perceived credibility and perceived self-efficacy. Normative pressure was found to be a weak determinant in explaining bank customers? intention to use mobile banking. The study also demonstrates the significant effect of perceived ease of use on behavioural intention through perceived usefulness.